Potensi Pengembangan Ekowisata di Kawasan Konservasi Lamun Trikora, Bintan, Kepulauan Riau - Ilham Ilahi; Aras Mulyadi; Dessy Yoswaty (Berkala Perikanan Terubuk, 2016)
Seagrass conservation area of Trikora has interesting natural resource and environment, so it has the potential to be developed for marine ecotourism sector. Development of ecotourism to the future requires comprehensive data. This research aims to providing data about the potential of marine ecotourism development in seagrass conservation area of Trikora, Bintan Regency, Kepulauan Riau Province. Survey was conducted at Teluk Bakau village, Malang Rapat village and Berakit village on 2016, August and September. Ecological parameters, seagrass vegetation structures, species of aquatic organism are very supportive marine ecotourism in these areas. Tourism Suitability Index (TSI) is at value of very appropriate, with Tourism Carrying Capacity (TCC) is 25.083 people per day or 175.581 people per week. Public perception about marine ecotourism development in these areas is good, especially on regional development and employment for local communities’ aspect.